Federal Practitioner 2021
DOI: 10.12788/fp.0119
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Fusion With Polyetheretherketone Rods Use for Patients With Degenerative Disease

Abstract: Polyetheretherketone (PEEK) rods for lumbar fusion have been available since 2007. However, literature about their utility is sparse and of mixed outcomes. Methods: A retrospective review of PEEK rod lumbar fusion cases was performed. Data were analyzed from 108 patients of the senior author Donald Ross who underwent PEEK lumbar fusion. Results: There were 97 single and 11 2-level fusions. Rates of tobacco use, diabetes mellitus, low bone density, depression, and immunosuppression were 23.1%, 24.1%, 14.8%, 32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…In terms of adverse events, Hirt et al [ 43 ] reviewed 462 patients and showed that the PEEK rod group was less likely to be readmitted due to adverse events. Ross et al [ 44 ] reviewed 108 patients and also showed a lower complication rate. None of the 15 studies we included reported any adverse events such as loosening of internal fixation, rupture, nerve injury, and infection.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of adverse events, Hirt et al [ 43 ] reviewed 462 patients and showed that the PEEK rod group was less likely to be readmitted due to adverse events. Ross et al [ 44 ] reviewed 108 patients and also showed a lower complication rate. None of the 15 studies we included reported any adverse events such as loosening of internal fixation, rupture, nerve injury, and infection.…”
Section: Discussionmentioning
confidence: 99%